2022
DOI: 10.1371/journal.pone.0269164
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on orthopaedic and traumatological care in Prague, the capital of the Czech Republic

Abstract: The coronavirus disease (COVID-19) has significantly affected society, especially healthcare systems worldwide. The aim of this retrospective study is to evaluate the impact of the COVID-19 pandemic on orthopaedic and trauma healthcare at the largest university hospital in the Czech Republic. The evaluated periods were in accordance with three waves of the disease and three respective lockdowns. To correlate the results, we evaluated the number of patients (inpatients and outpatients) treated in the same perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Patients may have faced lengthier appointment wait times, delayed responses to requests, or rushed sessions with their healthcare professionals. Furthermore, healthcare personnel under substantial stress may have been less attentive or compassionate towards patients, thus influencing patient satisfaction and perceptions of treatment quality [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Patients may have faced lengthier appointment wait times, delayed responses to requests, or rushed sessions with their healthcare professionals. Furthermore, healthcare personnel under substantial stress may have been less attentive or compassionate towards patients, thus influencing patient satisfaction and perceptions of treatment quality [26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Czechia showed that there was a significant decrease in healthcare services for orthopaedics and trauma patients due to the COVID-19 pandemic. In the same study, three different quarantine periods were compared with the same periods of three years before the pandemic, and the rates of orthopaedic outpatient clinic admissions were found to have decreased by 54.12%, 42.88% and 34.53%, in the first, second, and third lockdowns, respectively, and likewise, the number of elective surgeries had decreased by 69.01%, 87.57% and 74.89%, and the number of emergency surgeries by 33.15%, 37.46% and 27.24%, respectively [ 12 ]. In our study, the number of patients who were admitted to the outpatient clinic during the pandemic was found to have decreased by 40.29%, the number of patients admitted to the emergency service by 19.72%, and the number of patients undergoing operations by 35.37% (emergency surgeries decreased by 28.90% and elective surgeries by 37.72%).…”
Section: Discussionmentioning
confidence: 99%